Gallbladder disease and pancreatic cancer risk: a multicentric case-control European study. Issue 6 (November 2021) - Rosato, V.; Gómez-Rubio, P.; Molina-Montes, E.; Márquez, M.; Löhr, M.; O'Rorke, M.; Michalski, C. W.; Molero, X.; Farré, A.; Perea, J.; Kleeff, J.; Crnogorac-Jurcevic, T.; et al.
Abstract : Background and aims: The overall evidence on the association between gallbladder conditions (GBC: gallstones and cholecystectomy) and pancreatic cancer (PC) is inconsistent. To our knowledge, no previous investigations considered the role of tumour characteristics on this association. Thus, we aimed to assess the association between self-reported GBC and PC risk, by focussing on timing to PC diagnosis and tumour features (stage, location, and resection). Methods: Data derived from a European case-control study conducted between 2009 and 2014 including 1431 PC cases and 1090 controls. We used unconditional logistic regression models to estimate odds ratios (ORs) and corresponding 95% confidence intervals (CIs) adjusted for recognized confounders. Results: Overall, 298 (20.8%) cases and 127 (11.6%) controls reported to have had GBC, corresponding to an OR of 1.70 (95% CI 1.33–2.16). The ORs were 4.84 (95% CI 2.96–7.89) for GBC diagnosed <3 years before PC and 1.06 (95% CI 0.79–1.41) for ≥3 years. The risk was slightly higher for stage I/II (OR = 1.71, 95% CI 1.15–2.55) vs. stage III/IV tumours (OR = 1.23, 95% CI 0.87–1.76); for tumours sited in the head of the pancreas (OR = 1.59, 95% CI 1.13–2.24) vs. tumours located at the body/tail (OR = 1.02, 95% CI 0.62–1.68); and for tumours surgically resected (OR = 1.69, 95% CI 1.14–2.51) vs. non-resected tumours (OR = 1.25, 95% CI 0.88–1.78). The corresponding ORs for GBC diagnosed ≥3 years prior PC were close to unity. Conclusion: Our study supports the association between GBC and PC. Given the time-risk pattern observed, however, this relationship may be non-causal and, partly or largely, due to diagnostic attention and/or reverse causation. Abstract : Supplemental Digital Content is available in the text.